Kapitalisme dalam Kajian Ilmu Filsafat - Syeliana, Fera Alaida (Yayasan Sembilan Pemuda Indonesia, 2024)
This journal discusses the role of capitalism in the context of philosophy, exploring the philosophical, ethical and social implications that arise from this economic system. Capitalism, as a system based on private ownership and free markets, has had a profound impact on philosophical thought. This article attempts to identify and evaluate philosophical concepts that emerged along with the development of capitalism, as well as describe the role and criticism put forward by various related philosophical schools. Capitalism, as the dominant economic and social phenomenon in modern society, is the center of attention in philosophical studies. In this context, this journal takes a philosophical approach to explore the basic concepts of capitalism and their implications within the framework of philosophical thought. The research method used in this journal involves analysis of philosophical literature relating to capitalism. By examining classical and contemporary philosophical works, the journal seeks to summarize diverse views on capitalism and assess its impact on various aspects of human life.